PENAMPILAN HASIL DAN MUTU HASIL 12 GENOTIPE PADI RAWA PADA SAWAH LEBAK DAN SAWAH IRIGASI - JS Antromega Pratama; Mohammad Chozin; Marlin; Sumardi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[YIELD AND YIELD QUALITY PERFORMANCES OF 12 SWAMP RICE GENOTYPES ON LOWLANDSWAMPLAND AND IRRIGATED RICE FIELDS]. Development of rice varieties better adapted on swampland ecosystems is motivated by the increasing demand for staple food which has so far relied on irrigated paddy fields that are gradually decreased due to land conversion, while a vast available swampland has not been utilized optimally. The present study was conducted to compare the grain yield and milled grain qualities of twelve rice genotypes as grown on shallow lowland swampland and irrigated rice fields. A randomize complete block design with three replications was used in each agroecosystem to allocate ten rice elite lines (UBPR 1, UBPR 2, UBPR 3, UBPR 4, UBPR 6, UBPR 7, UBPR 8, UBPR 9, UBPR 10, UBPR 11) and two check swamp rice varieties (Inpara 4 and Inpara 6) on the experimental plots. The results showed that the grain yield and its contributing traits of the evaluated genotypes were generally lower when grown on lowland swampland rice field than those on irrigated rice field. Among the elite lines, UBPR 1, UBPR 2, UBPR 3, UBPR 4, UBPR 8, and UBPR 10 could serve as the alternative for the check varieties for lowland swampland production by having comparable performance in grain yield and its contributing traits, as well as the physical and chemical quality of the milled grains.